The interrelation of hyperboles with other stylistic devices in translation - Muladjanov, Shuxrat Fazlidinovich (The Lingua Spectrum, 2026)
Hyperbole is an indispensable attribute of both folk and authorial fairy tales, as it is highly emotional and expressive. However, despite this fact, the use of hyperbole in literary texts has not yet been studied in depth. The research conducted to date has focused on the meaning and functions of hyperbole in journalism, as well as in satirical and comic works. The purpose of this paper is to study this stylistic device using material from Russian and English-language authorial literary texts. The work involves an in-depth examination and analysis of examples of hyperbole usage in literary texts. The practical significance of the study lies in the fact that it can be used in the study of such academic disciplines as stylistics, comparative linguistics, and text linguistics. A comparative functional analysis of hyperbole was conducted in this study, based on the material of Russian and English-language literary fairy tales. The obtained results indicate that in the Russian fairy tales under analysis, exaggeration predominantly possesses a socially oriented and philosophically profound character, manifesting as a means of emphasizing acute social contradictions. In English-language fairy tales, however, hyperbole primarily serves expressive and stylistic purposes: it contributes to the creation of narrative dynamism, the vivid depiction of characters, and the formation of a unique atmosphere of magic, which is a genre-forming feature of the magical fairy tale.